8 - Male Violence against Women in Botswana: A Discussion of Gendered Uncertainties in a Rapidly Changing Environment - Godisang Mookodi (African Sociological Review, 2004)
Male violence against women has become commonplace in contemporary Botswana. Analyses ofgender-based violence in Botswana indicate that men are acting out their dominance through acts of violence. This dominance is created and reinforced by patriarchal belieJ:s and practices. The discussions are characterised by notions offemale victimhood and universal male dominance. This paper contextualises male violence against women by examining the role played by economic and social change in the shaping ofgender identities and relations. !show that white contemporary jàrms a/male dominance have resulted /rom their privi-leged access over time to resources such as wages and property, men also face uncertainties of' unemployment and reduced social status. l also show that rather than assuming the role of passive victims, women have developed, and continue to develop, contradictory survival strategies such as cohabitation and sexual relations that not only reinfàrce notions of male dominance but sometimes also challenge power relations and render some men victims.